(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research specialized in examining the role of guarantees and their impact on accounting benefits quality using statistical analysis to the income before and after the impact of guarantee on the accounting profits.This research depended on the inductive approach, which ensures that companies could manipulate in benefits through a variety of means including the guarantees. As it is possible that the companies can use the policy of guarantee as a strategy in business deal. The research aimed to highlight the different companies’ practices on policies guarantee and its impact on accounting benefits. The benefit of Dell Company has been chosen as a sample for the research because of the availability of interim data from the company for ten years from 2003 until 2013. The researcher depended on the use of a set of statistical tests for testing the presence of significant differences between income before and after the guarantee. The researcher found that analysis of guarantee is essential for decision-making of investors and have an important role in the control of the administration. the researcher recommended that guarantee (warranty) commitments in the financial database should be disclosed in the form of the notes as well as the statement of financial position. Thus, it will be clear to the accounting information user the size of the financial commitment to ensure that the proportion of the warranty sales.